Perancangan Game Edukasi Untuk Meningkatkan Pemahaman Belajar Siswa Kelas V SD Tentang Pendidikan Kewarganegaraan Berbasis Android - Nur Rambu Madik Anawaru; Yustina Rada; Tri Sari Dewi Novyanti Bertha Mira (Intellektika : Jurnal Ilmiah Mahasiswa, 2024)
The Mburukulu Elementary School in Mburukulu Village, Pahunga Lodu District, East Sumba Regency, is facing challenges in teaching Citizenship Education (PKN) in class V. The lack of interaction between teachers and students and the lack of student involvement has resulted in boredom, lack of focus, and lack of enthusiasm in Study. This research aims to create and implement an interactive educational game entitled "Student Explore" which was specifically developed for the Android platform. This game was designed using the Game Development Life Cycle (GDLC) methodology to ensure its quality and effectiveness in increasing student interaction and involvement in PKN learning in class V of SD Masehi Mburukulu. "Student Explore" is designed to provide an engaging and interactive learning experience for students. Through the educational games presented in the application, it is hoped that students can better understand the concepts taught in Citizenship Education. In its development, the GDLC method was used to ensure the game met expected quality standards and maximized its potential in enhancing learning. The benefits of this research include increasing students' interest in learning, better understanding of concepts, and support for teachers in the learning process. The result of this research is the implementation of educational games to improve students' learning understanding at SD Masehi Mburukulu. Thus, it is hoped that this game can be an effective solution to overcome challenges in PKN learning at the school.